Вы находитесь на странице: 1из 16

Задача 1. Написать разложение вектора x по векторам p, q, r .

1.1.

x   2, 4, 7 , p   0, 1, 2 , q   1, 0, 1 , r   1, 2, 4 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
0+h2-h3= -2
h1+0+2h3= 4
2h1+h2+4h3= 7

h1= 2
h2= -1
h3= 1

x= 2p-q+r

1.2.

x   6, 12, 1 , p   1, 3, 0 , q   2, 1, 1 , r   0, 1, 2 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1+2h2+0= 6
3h1-h2-h3= 12
0+h2+2h3= -1

h1= 4
h2= 1
h3= -1

x= 4p+q-r
1.3.

x   1, 4, 4 , p   2, 1, 1 , q   0, 3, 2 , r   1, 1, 1 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
2h1+0+h3= 1
h1+3h2-h3= -4
-h1+2h2+h3= 4

h1= -1
h2= 0
h3= 3

x= -p+3r

1.4.

x   9, 5, 5 , p   4, 1, 1 , q   2, 0, 3 , r   1, 2, 1 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
4h1+2h2-h3= -9
h1+0+2h3= 5
h1-3h2+h3= 5

h1= -1
h2= -1
h3= 3

x= -p-q+3r
1.5.

x   5, 5, 5 , p   2, 0, 1 , q   1, 3, 1 , r   0, 4, 1 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
-2h1+h2+0= -5
0+3h2+4h3= -5
h1-h2+h3= 5

h1= 1
h2= -3
h3= 1

x= p-3q+r

1.6.

x   13, 2, 7 , p   5, 1, 0 , q   2, 1, 3 , r   1, 0, 1 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
5h1+2h2+h3= 13
h1-h2+0= 2
0+3h2-h3= 7

h1= 3
h2= 1
h3= -4

x= 3p+q-4r
1.7.
x   19, 1, 7 , p   0, 1, 1 , q   2, 0, 1 , r   3, 1, 0 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
0-2h2+3h3= -19
h1+0+h3= -1
h1+h2+0= 7

h1= 2
h2= 5
h3= -3

x= 2p+5q-3r

1.8.

x   3, 3, 4 , p   1, 0, 2 , q   0, 1, 1 , r   2, 1, 4 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1+0+2h3= 3
0+h2-h3= -3
2h1+h2+4h3= 4

h1=1
h2= -2
h3= 1

x= p-2q+r
1.9.
x   3, 3, 1 , p   3, 1, 0 , q   1, 2, 1 , r   1, 0, 2 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
3h1-h2-h3= 3
h1+2h2+0= 3
0+h2+2h3= -1

h1=1
h2= 1
h3= -1

x= p+q-r

1.10.
x   1, 7, 4 , p   1, 2, 1 , q   2, 0, 3 , r   1, 1, 1 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
-h1+2h2+h3= -1
2h1+0+h3= 7
h1+3h2-h3= -4

h1=2
h2= -1
h3= 3

x= 2p-q+3r
1.11.
x   6, 5, 14 , p   1, 1, 4 , q   0, 3, 2 , r   2, 1, 1 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1+0+2h3= 6
h1-3h2+h3= 5
4h1+2h2-h3= -14

h1= -2
h2= -1
h3= 4

x= -2p-q+4r

1.12.
x   6, 1, 7 , p   1, 2, 0 , q   1, 1, 3 , r   1, 0, 4 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1-h2+h3= 6
-2h1+h2+0= -1
0+3h2+4h3= 7

h1= -1
h2= -3
h3= 4

x= -p-3q+4r

1.13.
x   5, 15, 0 , p   1, 0, 5 , q   1, 3, 2 , r   0, 1, 1 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1-h2+0= 5
0+3h2-h3= 15
5h1+2h2+h3= 0

h1= 4
h2= -1
h3= -18

x= 4p-q-18r

1.14.

x   2, 1, 11 , p   1, 1, 0 , q   0, 1, 2 , r   1, 0, 3 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1+0+h3= 2
h1+h2+0= -1
0-2h2+3h3= 11

h1= -3
h2= 2
h3= 5

x= -3p+2q+5r

1.15.
x   11, 5, 3 , p   1, 0, 2 , q   1, 0, 1 , r   2, 5, 3 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1-h2+2h3= 11
0+0+5h3= 5
2h1+h2-3h3= -3

h1= 3
h2= -6
h3= 1

x= 3p-6q+r

1.16.

x   8, 0, 5 , p   2, 0, 1 , q   1, 1, 0 , r   4, 1, 2 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
2h1+h2+4h3= 8
0+h2+h3= 0
h1+0+2h3= 5

h1= 1
h2= -2
h3= 2

x= p-2q+2r

1.17.
x   3, 1, 8 , p   0, 1, 3 , q   1, 2, 1 , r   2, 0, 1 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
0+h2+2h3= 3
h1+2h2+0= 1
3h1-h2-h3= 8

h1= 3
h2= -1
h3= 2

x= 3p-q+2r

1.18.

x   8, 1, 12 , p   1, 2, 1 , q   3, 0, 2 , r   1, 1, 1 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1+3h2-h3= 8
2h1+0+h3= 1
-h1+2h2+h3= 12

h1= -1
h2= 4
h3= 3

x= -p+4q+3r

1.19.
x   9, 8, 3 , p   1, 4, 1 , q   3, 2, 0 , r   1, 1, 2 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1-3h2+h3= -9
4h1+2h2-h3= -8
h1+0+2h3= -3

h1= -3
h2= 2
h3= 0

x= -3p+2q

1.20.
x   5, 9, 13 , p   0, 1, 2 , q   3, 1, 1 , r   4, 1, 0 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
0+3h2+4h3= -5
h1-h2+h3= 9
-2h1+h2+0= -13

h1= 5
h2= -3
h3= 1

x= 5p-3q+r

1.21.
x   15, 5, 6 , p   0, 5, 1 , q   3, 2, 1 , r   1, 1, 0 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
0+3h2-h3= -15
5h1+2h2+h3= 5
h1-h2+0= 6

h1= 2
h2= -4
h3= 3

x= 2p-4q+3r

1.22.

x   8, 9, 4 , p   1, 0, 1 , q   0, 2, 1 , r   1, 3, 0 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1+0+h3= 8
0-2h2+3h3= 9
h1+h2+0= 4

h1= 7
h2= -3
h3= 1

x= 7p-3q+r

1.23.
x   23, 14, 30 , p   2, 1, 0 , q   1, 1, 0 , r   3, 2, 5 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
2h1+h2-3h3= 23
h1-h2+2h3= -14
0+0+5h3= -30

h1= 1
h2= 3
h3= -6

x= p+3q-6r

1.24.

x   3, 1, 3 , p   2, 1, 0 , q   1, 0, 1 , r   4, 2, 1 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
2h1+h2+4h3= 3
h1+0+2h3= 1
0+h2+h3= 3

h1= -3
h2= 1
h3= 2

x= -3p+q+2r

1.25.
x   1, 7, 0 , p   0, 3, 1 , q   1, 1, 2 , r   2, 1, 0 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
0+h2+2h3= -1
3h1-h2-h3= 7
h1+2h2+0= 0

h1= 2
h2= -1
h3= 0

x= 2p-q

1.26.
x   11, 1, 4 , p   1, 1, 2 , q   3, 2, 0 , r   1, 1, 1 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1+3h2-h3= 11
-h1+2h2+h3= -1
2h1+0+h3= 4

h1= 3
h2= 2
h3= -2

x= 3p+2q-2r

1.27.
x   13, 2, 18 , p   1, 1, 4 , q   3, 0, 2 , r   1, 2, 1 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1-3h2+h3= -13
h1+0+2h3= 2
4h1+2h2-h3= 18

h1= 2
h2= 5
h3= 0

x= 2p+5q

1.28.
x   0, 8, 9 , p   0, 2, 1 , q   3, 1, 1 , r   4, 0, 1 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
0+3h2+4h3= 0
-2h1+h2+0= -8
h1-h2+h3= 9

h1= 2
h2= -4
h3= 3

x= 2p-4q+3r

1.29.
x   8, 7, 13 , p   0, 1, 5 , q   3, 1, 2 , r   1, 0, 1 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
0+3h2-h3= 8
h1-h2+0= -7
5h1+2h2+h3= -13

h1= -4
h2= 3
h3= 1

x= -4p+3q+r

1.30.

x   2, 7, 5 , p   1, 0, 1 , q   1, 2, 0 , r   0, 3, 1 .

x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
h1+h2+0= 2
0-2h2+3h3= 7
h1+0+h3= 5

h1= 4
h2= -2
h3= 1

x= 4p-2q+r

1.31.
x   15, 20, 1 , p   0, 2, 1 , q   0, 1, 1 , r   5, 3, 2 .
x= h1p+h2q+h3r
Найдем h1, h2 и h3 из системы уравнений
0+0+5h3= 15
2h1+h2-3h3= -20
h1-h2+2h3= -1

h1= -6
h2= 1
h3= 3

x= -6p+q+3r